Pengalaman dan Pengajaran Iman Ketakase Menurut Paus Fransiskus - Paul Budi Kleden (Sekolah Tinggi Pastoral Atma Reksa Ende, Jalan Gatot Subroto, KM 3. Tlp./Fax (0381) 250012, 2016)
Pope Francis pays a serious attention towards cathecists. The catechists have become lay apostles to help the priests in translating the Word of God into people’s life contects. The significance of the role of the cathecists has made them one of the main subjects in the promotion of christian faith. In conection with this Pope Francis again and again reminds us in his Evangelii Gaudium apostolic exhortation that the most important truth about the cathecism, is that every cahtecism activity should “begin with Christ”. Jesus Christ shoud be the starting point of the teaching rendered by a cathecist.